Short‐term intervention to reduce anxiety before coronary artery bypass surgery – a randomised controlled trial. Issue 3 (February 2016) - Heilmann, Claudia; Stotz, Ulrike; Burbaum, Christina; Feuchtinger, Johanna; Leonhart, Rainer; Siepe, Matthias; Beyersdorf, Friedhelm; Fritzsche, Kurt
Abstract : Aims and objectives: The aim of this study was to evaluate an intervention with individualised information and emotional support before coronary artery bypass grafting in a controlled randomised trial. Background: Anxiety is a typical phenomenon in patients who are to undergo cardiac surgery. Preoperative anxiety has been shown to correlate to adverse postoperative outcomes. Emotional support could be an effective measure to reduce preoperative anxiety. Design and methods: Patients with planned first coronary artery bypass grafting were randomised into an intervention group ( n  = 139) and a control group ( n  = 114). The patients of the control group were routinely informed as usual. The patients of the intervention group received a dialogue with individualised information and emotional support one day before surgery in addition to standard care. This intervention of ~30 minutes was based on a supportive psychotherapy model and was delivered by trained nurses. The primary outcome was the change in anxiety before operation. The secondary outcomes consisted of changes in postoperative anxiety, time on intensive care unit and in‐hospital mortality. Results: Significantly reduced anxiety was found in the intervention group patients compared to control patients before coronary artery bypass grafting ( p  < 0·001) and five days after surgery ( p  < 0·001). Both groups did not differ in in‐hospital mortality and duration of stay in the intensive care unit. Conclusions: Our short‐term psychosocial intervention in patients undergoing coronary artery bypass grafting had a beneficial effect on reducing pre‐ and postoperative anxiety that was better than routine information alone. Relevance to clinical practice: These results advocate training for nurses and physicians to provide emotional support to patients before coronary artery bypass grafting.